Capacity Building, Knowledge Enhancement, and Consultative Processes for Development of a Digital Tool (Ni-kshay SETU) to Support the Management of Patients with Tuberculosis: Exploratory Qualitative Study - Harsh Shah; Jay Patel; Sandul Yasobant; Deepak Saxena; Somen Saha; Anish Sinha; Priya Bhavsar; Yogesh Patel; Bhavesh Modi; Pankaj Nimavat; Dixit Kapadiya; Manish Fancy (Journal of Medical Internet Research, 2023)
This study aimed to explore the development and evolution of a mobile health tool for capacity building of the Indian health system's workforce to better manage patients with TB.
Keywords: Euclidean mistance method; Physical health infrastructure; Public health resource